Tallinn manual 2.0 on the international law applicable to cyber operations / Prepared by the International Group of Experts at the Invitation of the NATO Cooperative Cyber Defence Centre of Excellence ; general rditor Michael N. Schmitt ; managing editor Liis Vihul. - Schmitt, Michael N. (Cambridge University Press, 2017)
Tallinn Manual 2.0 expands on the highly influential first edition by extending its coverage of the international law governing cyber operations to peacetime legal regimes. The product of a three-year follow-on project by a new group of twenty renowned international law experts, it addresses such topics as sovereignty, state responsibility, human rights, and the law of air, space, and the sea. Tallinn Manual 2.0 identifies 154 'black letter' rules governing cyber operations and provides extensive commentary on each rule. Although Tallinn Manual 2.0 represents the views of the experts in their personal capacity, the project benefitted from the unofficial input of many states and over fifty peer reviewers.